The Analysis of Junior High School Students' Mathematical Connection on The Ratio and Proportion Concepts - Ismiyanti Suci Pratiwi; Eyus Sudihartinih (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
The purpose of this study was to obtain an overview of the mathematical connections of junior high school students on the concepts of ratio and proportion. This research uses a descriptive qualitative method with data triangulation. The research participants were four junior high school students in Sukabumi. The instrument used in this study consisted of a description test of three questions that had been consulted with experts and based on considerations regarding indicators of mathematical connection ability. Based on the results of the study, it is known that the ability of students to recognize and use connections between mathematical ideas is 50%, the ability of students to connect and apply mathematical concepts with other disciplines is 50%, and the ability of students to connect and apply mathematical concepts to problems in everyday life with a percentage of 50%. The results showed that the mathematical connection ability of some junior high school students in Sukabumi on the concept of comparison was included in the poor category.